Maternal Zinc Diet Impairs Learning and Memory in Offspring Rats through the CREB/BDNF Pathway - Novi Dewi Tanjung; Nieka Adhara Wahono; Ninik Mudjihartini; Ani Retno Prijanti (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Zinc released into the synaptic cleft able to modulate various signaling pathways, including brain derived neurotrophic factor (BDNF) and its receptor tropomyosin receptor kinase B (TrkB). Zinc binding to its receptor, G-protein coupled receptor 39 (GPR39), may trigger biochemical pathways leading to cAMP response element binding protein (CREB)-dependent gene transcription that subsequently promotes BDNF upregulation. Therefore, zinc dyshomeostasis should be considered as a condition that induces disruption of CREB/BDNF signaling. This study was conducted to examine the effect of maternal zinc diet on hippocampal expression levels of CREB and BDNF in offspring.METHODS: One-day pregnant rats were randomly divided into five groups: zinc-deficient (D), zinc-restricted (R), zinc-adequate (A), zinc-supplemented (S), and excess zinc-supplemented (ES). The groups had different zinc diets during pregnancy and lactation. The behavioral function of the offspring was tested with Y-maze at the 43th postnatal. Hippocampus was isolated, BDNF was assessed by quantitative real-time polymerase chain reaction (qRT-PCR), and CREB was examined using sandwich enzyme-linked immunosorbent assay (ELISA).RESULTS: Spatial working memory measurement demonstrated that D and ES group exhibited a significantly lower spontaneous alternation than other groups. The qRT-PCR and ELISA analysis revealed the hippocampal expression level of BDNF and CREB decreased in groups D and ES, but tended to increase in groups R and S, until the highest expression peak was found in group A.CONCLUSION: High and low intake of zinc induces lower expression of BDNF and CREB in hippocampus, which further impairs learning and memory. Our findings suggest the signaling pathway of CREB/BDNF is involved in zinc dyshomeostasis-induced cognitive impairments.KEYWORDS: hippocampus, BDNF, CREB, TrkB, GPR39, zinc, diet, LTP